Alterations in the balance of tubulin glycylation and glutamylation in photoreceptors leads to retinal degeneration - Bosch Grau, Montserrat; Masson, Christel; Gadadhar, Sudarshan; Rocha, Cecilia; Tort, Olivia; Marques Sousa, Patricia; Vacher, Sophie; Bieche, Ivan; Janke, Carsten (Journal of cell science, 2017)
Tubulin is subject to a wide variety of posttranslational modifications, which, as part of the tubulin code, are involved in the regulation of microtubule functions. Glycylation has so far predominantly been found in motile cilia and flagella, and absence of this modification leads to ciliary disassembly. Here, we demonstrate that the correct functioning of connecting cilia of photoreceptors, which are non-motile sensory cilia, is also dependent on glycylation. In contrast to many other tissues, only one glycylase, TTLL3, is expressed in retina. Ttll3−/− mice lack glycylation in photoreceptors, which results in shortening of connecting cilia and slow retinal degeneration. Moreover, absence of glycylation results in increased levels of tubulin glutamylation in photoreceptors, and inversely, the hyperglutamylation observed in the Purkinje cell degeneration (pcd) mouse abolishes glycylation. This suggests that both posttranslational modifications compete for modification sites, and that unbalancing the glutamylation–glycylation equilibrium on axonemes of connecting cilia, regardless of the enzymatic mechanism, invariably leads to retinal degeneration.